Current results: Integration of Youth in Dubrava - Ognjen Čaldarović, Sonja Podgorelec, Carmen Brčić, Melita Švob (Array, 2006)
Current results and changes in the socialization and integration of Croatian youth, in the school in part of Zagreb- Dubrava ( known as a multiethnic and multicultural society). Special test has been developed for the measure of the popularity of piers and analysis of that phenomena.